International migration, remittances and labour supply: The case of the Republic of Haiti - Evans Jadotte (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
The Republic of Haiti is a prime international remittance-recipient country in the Latin American and Caribbean (LAC) region, relative to its gross domestic product (GDP). The downside of this fact may be that Haiti, based on population size, is also the largest exporter of skilled workers in the world. The present research uses a zero-altered negative binomial (with logit inflation) to model the international migration decision-process of households, and endogenous regressors' Amemiya generalized least squares method (instrumental variable Tobit, IV-Tobit) to account for selectivity and endogeneity issues to assess the impact of remittances on labour market outcomes. The results in terms of a decline of labour supply in the presence of remittances are in line with those observed thus far in the literature. However, the impact of international remittances does not seem to be important in determining the labour participation behaviour, particularly for women, in the recipient households.
Keywords: C39; F22; F24; J22; 330; Republic of Haiti; international migration; remittances; labour supply; Internationale Arbeitsmobilität; Rücküberweisung (Migranten); Arbeitsangebot; Haiti